The comparison of balance abilities of novice, mid-level and elite archers during arrow shooting - Yenigelen Simsek, D. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Archery is a good example of a sport where balance is required to achieve high scores. (Hrysomallis, 2011). The aim of this study was to compare the differences in ground reaction forces between novice, mid-level and elite archers during arrow shooting. Methods: Twenty-seven archers (group I: elite archers (EA): n=9, group II: mid-level archers (MLA): n=9, group III: novice archers (NA): n=9) volunteered to participate to the current study. The archery level have divided in to three groups (elite archers > 1200, mid-level 1100-1200, novice archers <1100) according to their FITA scores. Anterio-posterior (fy) and Medio-lateral (fx) force and center of pressure (COP) sway values during the successful shots towards the goal from a distance of 18 m have been analyzed. During measurement 600x400x100 mm`Kistler (Germany) 9281EA` force platform have used. Force data sampled at 2000 Hz and normalized according to body weight. ANOVA test has been applied to determine the ground reaction force differences that emerge throughout the implementation of the arrow shot techniques of the elite, mid-level and novice archers and Tukey-W test as the PostHoc test has been chosen to present from which group the differences stem. Results: The highest sway values have been demonstrated by novice archers (fy range value = 0,0495; fx= 0,0524) as compared with elite (fy range value = 0,036; fx=0,376) and mid-level archers (fy range value = 0,0404; fx= 0,0430). Midlevel archers have shown least sway. On the other hand elite archer`s sway strategy was different than both archery groups. Just after a sharp increase, they have reached a plateau on than continue swaying on anterior-posterior directions. Discussion: In general, the results of these studies revealed that balance point projection of archers, in terms of the area they occupy during shooting, the elite archers showed an sway towards right or left sides, but the amount of sway towards front and back was relatively less. It was observed from current and the other study`s that as the performance level decreased the movements towards front and back increased. This situation is thought to be a factor decreasing the score at the target. It can be derived from these results that as the archers get experienced through technical development and shooting trainings postural sway rates at fx and fy sides will decrease. The experienced archers were observed to manage to stabilize their postures better even at the last seconds of shooting. In order to train archers in the case of keep balance just before arrow release instantaneous visual force feedback training including fx, fy and COP sway values could be recommended.